Acomparison between prostaglandin E1 and oxytocin in termination of medical pregnancy (in term pregnancy) - al-Nukari, Mohamnad; Saleh, Hasan; al-Johni, Hasan (Latakia University Journal -Medical Sciences Series, 2020)
Objective:to clear the effect of misoprostol (prostaglandin E1) 50 mcg/4 hours vaginality in induction of labour to terminate pregnancy medically in both primigravide and multigravide in comparison with oxytocin and to concentrate on the complication that may occur during induction . Methods:our stady is future interventional study . the study took in the labour room of the hospital of tishreen university ,during the period between 2018-2019 . 80 patients were included. Misoprostol 50 mcg vaginality was used for induction of labour in 40 patients . and oxytocin intravenously was used for induction in the other 40 patients. Results:it was clear from our study that prostaglandin E1 is more effective than oxytocin in induction of labour and termination pregnancy from where succsed induction and reducing the number of cesarean sections . هدف البحث : معرفة مدى فعالية الميزوبروستول (البروستاغلاندين E1) بجرعة 50مكغ/4 ساعات مهبليا في تحريض المخاض لإنهاء الحمل الطبي لدى الخروسات والولودات بمقارنته مع الأوكسيتوسين وتبيان المضاعفات التي قد تحدث في أثناء التحريض . الطرائق : أجريت دراسة وهي دراسة تداخلية مستقبلية في قسم المخاض بمستشفى تشرين الجامعي في مدينة اللاذقية خلال 2018-2019 حيث تم تطبيق تحريض إنضاجي (على عنق رحم ناضج ) لدى 80 سيدة مستطب إنهاء الحمل لديهن . استخدم البروستاغلاندين E1(الميزوبروستول ) بجرعة 50مكغ مهبليا عند 40 سيدة ، وطبق الأوكسيتوسين تسريب وريدي لدى 40 سيدة أخرى . النتائج : تبين من خلال الدراسة أن تطبيق البروستاغلاندين E1 كان ذا نتائج أفضل من تطبيق الأوكسيتوسين في تحريض المخاض وانهاء الحمل من حيث نجاح التحريض ومن حيث إنقاص نسبة القيصريات .